REAKTUALISASI PERLINDUNGAN PEREMPUAN DALAM HUKUM KELUARGA ISLAM DI ARAB SAUDI DAN MESIR - Sofiana, Neng Eri; Meiningtias , Dian (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2023)
The actualization of Islamic family law is a manifestation of legal reform in regulations, fatwas, and legislation, so that it can keep up with the times, and is more effective and more useful. Within the scope of the state, ulama's ijtihad and legislative policies are the basis for reforming Islamic family law, so that the actualization of the law is expected not only to suit the needs of the times but also to be the basis for the people to move forward. This research is presented in three areas of Muslim countries, namely Saudi Arabia, and Egypt. The two Muslim countries were chosen because of their work in the world and their position which is often a barometer of policy and reform of Islamic law in other countries. Furthermore, this study looks at how the two countries provide protection to women in family law reform and how the typology in family law reform is carried out with a literature study with data obtained from related literature and descriptive analysis and obtains the results that family law reform in Saudi Arabia there are still many polemics and problems that harm women, so efforts are needed to re-accredit family law reforms that can protect women, while in Egypt, efforts to protect women in family law have begun, but have not touched all aspects of family law.